Bibliografia prasy i kalendarzy sportowych w zbiorach Biblioteki Jagiellońskiej: Lata 1841-1956 - Cichosz, Marcin (2024)
BIBLIOGRAPHY OF PRESS AND SPORTS CALENDARS IN THE COLLECTION OF THE JAGIELLONIAN LIBRARY YEARS 1841-1956Sport and physical culture as a whole were, at their origins, a relatively narrow fringe of social life. Hence the activity of collecting, preserving and making available sources on sport and physical education was often underestimated. For this reason, the press relating to these areas is an extremely valuable and often the only source for learning the history of sport in Polish lands. The bibliography covers the period from the publication of the report Sprawozdanie o Wyścigach Konnych i Wystawie Zwierząt Gospodarskich w Królestwie Polskiém w Roku 1841 Odbytych to the changes that took place in Poland in 1956 and had a definite impact on the development and character of the Polish sports press. The territorial coverage includes the current borders of the Polish state in the west and the north, and the borders from before the first partition in 1772 in the east. In addition, the bibliography records sports magazines published in Polish between 1841 and 1956 throughout the world. The selection of magazines for the bibliography includes publications meeting the criteria contained in the definition of the sports press in Encyklopedia wiedzy o prasie. The introduction outlines the state of research on the Polish sports press and presents the fundamental aim of the work, which was to supplement the research output with hitherto unpublished information on periodicals in this field and to present these publications held in the Jagiellonian Library collections to a wider audience. Relevant definitions functioning in science are juxtaposed and the choice of each of them is justified. The structure of the description has been designed to make it as easy as possible for the reader to use the information contained in each article. In its main part, the bibliography records 434 titles of sports periodicals. It also includes publications such as supplements, reports, membership lists and directories, and internal bulletins of clubs, associations and sports societies. These kinds of materials have been largely ignored by sports press researchers, though they are an important source for the history of sports organizations in the 19th and 20th centuries. A separate group are calendars, which for practical reasons have also been included in the bibliography. The study has been enriched by an appendix of 37 items, which includes some of the titles rejected as a result of my selection, with a more detailed argumentation. The bibliography is completed by respective indexes of persons, institutions and places.
Keywords: bibliography; sports press (1841-1956); Polish sports press in exile (1841- 1956); Poland; Polish lands; Jagiellonian Library